Peran Usaha Mikro, Kecil, Dan Menengah (UMKM) Kerajinan Kendang Dalam Meningkatkan Kesejahteraan Masyarakat Sentul ( Studi Kasus Masyarakat Di Desa Santren Kelurahan Sentul Kecamatan Kepanjenkidul Kota Blitar ) - Hidayatulloh, Habib; Wahono, Budi; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The role of micro, small and medium enterprises (UMKM) to Indonesia’s economy is evident in several aspects: (1) they save as key actors across various economic sectors, (2) they represent the largest source of employment, (3) they play a vital role in fostering local economic growth and empowering communities, (4) they help generate new market opportunities and drive innovation, and (5) they support the nation’s balance of payments through their involvement in export activities. One of the largest UMKM and a mainstay industry is the Kendang UMKM in Sentul Village, Blitar City. The purpose of this study was to determine the role of the Kendang UMKM in Sentul on the welfare of the people of Sentul Village, Kepanjenkidul District, Blitar City. Based on the results of observations and interviews, it can be concluded that the decline in UMKM turnover in Kepanjenkidul District was due to the pandemic factor so that demand from overseas markets was hampered. There are three indicators that have been chosen to determine the role of the Kendang UMKM in improving the welfare of the people in Sentul Village. First, the equalization of the level of the economy of the common people. The second indicator is the reduction in poverty levels. The third indicator is the decreasing number of unemployed. Keywords: UMKM, Kendang, Blitar, Economy